Organisations paysannes : Un levier pour développer l'agriculture de conservation au Maghreb - Vadon B.; Lamouchi L.; Elmay S.; Mahnane S.; Benaouda H.; Elgharras O. (Troisièmes rencontres méditerranéennes du semis direct, 2006)
Farmers in the Maghreb countries have been interested in 'no till' cropping systems since the late 90's. Three groups involved in direct drilling or minimum tillage in Tunisia, Morocco and Algeria are described here. Their example proves that 'fellahs' can come together and thus break off their isolation, they can share their know-how and manage collective equipment in order to lower their costs. With the help of research and public support, these farmers' organizations are the most efficient way to enable Conservation Agriculture extension in all the areas subject to low rainfall, erosion and now under the pressure of the world trade.
3. Mediterranean Meeting on no Tillage, 2006/03/23-25, Zaragoza (Spain)